2010
DOI: 10.1097/wox.0b013e3181e61ebf
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ids in Allergy: Timeliness of a Classic Concept

Abstract: Abstract:Anti-idiotypic antibodies (anti-ids) are part of natural immune responses with regulatory capacity. Their effect on an antigen-specific, so-called Ab1 antibody response, is dependent on 1) the original antigen, which they mirror, being Ab2 antibodies, and 2) their isotype. In the case of IgE-mediated allergy, natural anti-ids against allergen-specific IgE represent internal images of allergen molecules. A key biologic feature of allergens is that they can crosslink IgE, expressed by B-lymphocytes or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
0
15
1
Order By: Relevance
“…This would be in contrast to our findings with mimotopes from random peptide libraries which were devoid of T-cell stimulatory capacities [26,27]. It is even conceivable that they directly activate T-cells as it has been repeatedly demonstrated that B- and T-cell receptors may share the same idiotypes [6,9]. These aspects should be addressed in future functional studies.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…This would be in contrast to our findings with mimotopes from random peptide libraries which were devoid of T-cell stimulatory capacities [26,27]. It is even conceivable that they directly activate T-cells as it has been repeatedly demonstrated that B- and T-cell receptors may share the same idiotypes [6,9]. These aspects should be addressed in future functional studies.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, mimotope vaccines usually lack T-cell epitopes [26,27] and thus may be advantageous when inflammation caused by activation of allergen-specific T-cells has to be avoided [37]. Mimotopes can be readily selected from phage display libraries presenting peptides, Fab-fragments or hairpin libraries by screening them with antigen specific antibodies (reviewed by [6]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that immunoglobulin could be the specific blood component mediating the therapeutic efficacy of ABT in patients with AD. Induction of an anti-idiotype immune response (immune response to the antigen-binding portion of immunoglobulin) has long been suggested as the main mechanism of the development of immune tolerance in allergic and autoimmune diseases [18,19]. The possibility of involvement of an anti-idiotype mechanism in the development of the therapeutic efficacy of ABT or AHPT should be further evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neutralizing secreted antibody, anti-Id can also down-regulate the secretion of the idiotypic antibody [31,32]. This effect is only observed at high concentrations of anti-Id.…”
Section: Anti-id In the Idiotypic Networkmentioning
confidence: 99%